Wound Dressings Based on Sodium Alginate-Polyvinyl Alcohol-Moringa oleifera Extracts - Samir Kamel; Sawsan Dacrory; Peter Hesemann; Nadir Bettache; Lamiaa M. A. Ali; Lou Postel; Engy M. Akl; Mohamed El-Sakhawy (MDPI AG, 2023)
Biopolymers have significant pharmaceutical applications, and their blending has favorable characteristics for their pharmaceutical properties compared to the sole components. In this work, sodium alginate (SA) as a marine biopolymer was blended with poly(vinyl) alcohol (PVA) to form SA/PVA scaffolds through the freeze-thawing technique. Additionally, polyphenolic compounds in Moringa oleifera leaves were extracted by different solvents, and it was found that extracts with 80% methanol had the highest antioxidant activity. Different concentrations (0.0-2.5%) of this extract were successfully immobilized in SA/PVA scaffolds during preparation. The characterization of the scaffolds was carried out via FT-IR, XRD, TG, and SEM. The pure and Moringa oleifera extract immobilized SA/PVA scaffolds (MOE/SA/PVA) showed high biocompatibility with human fibroblasts. Further, they showed excellent in vitro and in vivo wound healing capacity, with the best effect noted for the scaffold with high extract content (2.5%).